Influence of word of mouth location and atmosphere of the room to decision - Agustini Tanjung; Rahmat Hidayat (STIE Binaniaga, 2021)
This research will discuss about there is a influence between WOM, location, and atmosphere of the room to the purchase decision in the coffee shop room longing, given the number of visitors who come when there are many coffee shops in Cikarang. WOM that we know the communication from word of mouth is a communication process in the form of either individual or group recommendations on a product or a service aimed at providing personal information. The location in relation to marketing activities is a special and interesting place because the land can be used to shop a variety of needs. There are several factors of atmospheric stores that could affect emotions, behaviors or purchasing decisions. These factors include exterior, layout and interior. The decision on the purchase of a product is influenced by many factors, aimed at fulfillment of needs and desires Researchers will use the entire coffee shop visitors as a population and will use 50 people as respondents, to collect data so that researchers will spread the questionnaire against visitors and then the data will be researchers using linear regression analysis techniques